Review Meibomian Gland Dysfunction: Emerging Diagnostic Technologies and Novel Therapeutic Approaches - Brajan Roczyński; Izabela Polok; Oliwia Pniewska; Paulina Polok (Journal of Education, Health and Sport, 2026)
Meibomian gland dysfunction (MGD) is a chronic disorder of the eyelid margin and the leading cause of evaporative dry eye disease (EDE). Alterations in meibum secretion impair tear film stability, increase tear evaporation, and contribute to ocular surface inflammation and visual disturbances. This narrative review summarizes current knowledge regarding the anatomy and physiology of the meibomian glands, the pathophysiology of MGD, its relationship with dry eye disease (DED), contemporary diagnostic methods, and available treatment options. Recent advances in meibography, interferometry, lipid layer assessment, and artificial intelligence have improved diagnostic capabilities. In addition to conventional therapies, including eyelid hygiene, warm compresses, and anti-inflammatory treatment, device-based interventions such as thermal pulsation therapy, intense pulsed light, and low-level light therapy have expanded therapeutic possibilities. Emerging regenerative approaches may further improve future management strategies. Continued advances in diagnosis and treatment are expected to support more personalized and mechanism-based care for patients with MGD.